The macroeconomic implications of zero growth: A post-Keynesian approach - Eckhard Hein; Valeria Jimenez (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This paper tries to clarify some important aspects around the zero-growth discussion. Starting from an accounting perspective, we analyse the implications of zero growth and clarify the stability conditions of such an economy. This is complemented with a monetary circuit approach - which, like any model, has to respect the national income and financial accounting conventions. The latter allows us to show that a stationary economy, i.e an economy with zero net investment, is compatible with positive profits and interest rates. It is also argued that a stationary economy does not generate systemic financial instability, in the sense of rising or falling financial assets- or financial liabilities-income ratios, if the financial balances of each macroeconomic sector are zero. In order to analyse the dynamic stability of such an economy, we make use of an autonomous demand-led growth model driven by government expenditures. We show that a stable stationary state with zero growth, positive profits, and a positive interest rate is possible. However, the stable adjustment of government expenditure-capital and government debt-capital ratios to their long-run equilibrium values requires specific maxima for the propensity to consume out wealth and for the rate of interest, assuming a balanced government budget and zero retained earnings of the firm sector.
Keywords: Q01; O44; P10; 330; Ecological macroeconomics; post-Keynesian economics; stationary-state economics; growth imperative